2015
DOI: 10.1007/s10681-015-1466-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL for ear row number and two-ranked versus many-ranked ear in maize across four environments

Abstract: Ear row number (ERN) is not only a key trait involved in maize (Zea mays L.) evolution but also an important component directly related to grain yield. In this report, 325 recombinant inbred lines (RILs, F 6:7 ) derived from a cross between B73 with 16 rows and SICAU1212 with four rows (two-ranked with two rows per rank) were utilized to detect quantitative trait loci (QTL) associated with ERN and two-ranked versus many-ranked ears (TR). Compared to modern maize that formed approximately 8-20 rows, SICAU1212 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 79 publications
(105 reference statements)
1
25
0
Order By: Relevance
“…One pair of epistatic interaction involved in region near qHKW2-1 has been identified for GY under water-stressed conditions . Stable epistatic interactions involved in bin 2.03 region were detected for kernel row number in different environments (Cai et al 2014;Yang et al 2015). Sa et al (2015) showed that genetic interactions involved in bin 2.03 region were associated with plant height and HKW.…”
Section: Epistasis Between Qtlmentioning
confidence: 93%
“…One pair of epistatic interaction involved in region near qHKW2-1 has been identified for GY under water-stressed conditions . Stable epistatic interactions involved in bin 2.03 region were detected for kernel row number in different environments (Cai et al 2014;Yang et al 2015). Sa et al (2015) showed that genetic interactions involved in bin 2.03 region were associated with plant height and HKW.…”
Section: Epistasis Between Qtlmentioning
confidence: 93%
“…ERN is one of the key traits that distinguish maize and teosinte (Doebley, 2004). QTL mapping has been conducted in many studies, and a large number of QTLs have been identified for ERN across generations and environments in all10 maize chromosomes (Doebley et al, 1990;Doebley andStec, 1991, 1993;Veldboom and Lee, 1994;Austin and Lee, 1996;Szabó and Burr, 1996;Upadyayula et al, 2006;Yan et al, 2006;Briggs et al, 2007;Li et al, 2007;Guo et al, 2008;Karen Sabadin et al, 2008;Li et al, 2011;Lu et al, 2011;Cai et al, 2014;Lemmon and Doebley, 2014;Li et al, 2014;Tian et al, 2014;Yang et al, 2015). In this study, three QTLs (qERN2-1, qERN4-2, and qERN8-1) were consistently associated with ERN.…”
Section: Discussionmentioning
confidence: 99%
“…The first QTL, qERN2-1 (bin 2.02), was also located onthe short segment of chromosome 2, indicating a potential QTL region near qERN2-1 that may not only play a novel role in affecting ERN during maize domestication (Doebley andStec, 1991, 1993), but may also be associated with ERN during later improvement processes. The second QTL (qERN4-2 at bin 4.08) significantly affects ERN (Austin and Lee, 1996;Li et al, 2011;Lu et al, 2011;Yang et al, 2015). In the genetic region of bin 4.08, one major QTL for ERN has been identified in an F 2:3 population, and explained the largest percentage (16.4%) of ERN variation (Cai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits are quantitatively inherited and influenced by genotypes, environments, and environment-by-genotype interactions. The KRN significantly contributes to grain yield and has the highest broad-sense heritability ( H 2 ) among the three components [2, 3]. Therefore, the investigation into the genetic architecture underlying KRN is helpful not only for understanding the genetic mechanisms underlying ear development but also for improving the maize grain yield.…”
Section: Introductionmentioning
confidence: 99%